The unknown Hsüan-tsang - Devahuti, D. (New Delhi ; New York : Oxford University Press, 2001)
Biographical account of Xuanzang, ca. 596-664, a Chinese Buddhist monk who visited India in the seventh century A.D.
Machine generated contents note: Preface -- Foreword -- INTRODUCTION: THE UNKNOWN HSUAN-TSANG -- 1 THE LIFE OF HSUAN-TSANG -- 2. HSUAN-TSANG, PRAJNA-DEVA, JNANA-PRABHA -- CORRESPONDENCE -- A. From the Chinese Text of the Life of Hsiian-tsang -- B. From the Uigur Text of the Life of Hsiian-tsang -- Letters of the Biography of Hsiian-tsang in Uigurish -- English translation of parts of Briefe der Uigurischen -- Hiien-tsang Biographie by Annemarie Von Gabain: -- Introduction -- Observations -- Index -- 3. RESUME OF CHAPTERS SIX-TEN OF THE LIFE -- (Translated from the Histoire de la vie de Hiouen-thsang -- et de ses Voyages dans l'lnde by S. Julien) -- Chapter Seven -- Chapter Eight -- Chapter Nine -- Chapter Ten -- Julien's Notes to His R6sum6 of Life -- 4. THE GENERAL ACCOUNT OF INDIA IN THE TA T'ANItffls -- YU CHI (Records of the Western Lands of the Great -- T'ang Period) -- Introduction -- The General Descriptio of Idi -- Kie-jo-kio-she-kw6 (Kanyakubja) -- Devahuti's Notes on Kanyakubja -- Appendix: Inventory of the Complete Works of Hsiian- -- tsang -- Buddhist Texts Translated by Hsiian-tsang Listed in -- Chronological Order -- Buddhis Texts Translated bysiian-tsang Listed in -- Alphabetical Order -- BIBLIOGRAPHY -- INDEX -- PLATES.
Includes bibliographical references (p. [168]-170) and index.
Keywords: Xuanzang, -- approximately 596-664.; Buddhist priests -- China -- Biography